Emergency Department Slit Lamp Interdisciplinary Training Via Longitudinal Assessment in Medical Practice. - Hamou, Samara; Ghiaee, Shayan; Chung, Christine; Lloyd, Maureen; Khem, Kelly; Xiao Chi Zhang (Western Journal of Emergency Medicine: Integrating Emergency Care with Population Health, 2024)
Introduction: Eye emergencies make up nearly 3% of US emergency department (ED) visits. While emergency physicians (EP) should diagnose and treat these ophthalmologic emergencies, many trainees report limited ocular exposure and insufficient training throughout their residency to confidently conduct a thorough slit-lamp exam. Methods: We created an interdisciplinary, simulation-based mastery learning (SBML) curriculum to teach emergency attending physicians how to operate the slit lamp with multimodal learning methodology at a tertiary academic center. The EPs first demonstrate their initial slit-lamp competency with a 20-item checklist, and they then review the necessary curricular content to pass their independent readiness test before completing their in-person teaching and demonstration session with an ophthalmology attending to demonstrate procedural mastery (minimal passing score >90%). Results: Fifteen EPs were enrolled; all completed the final exam of the curriculum. The pre- and postcurriculum checklist scores increased by an average of seven points (P = .002); 86.7% of EPs felt confident in completing a slit-lamp exam after the curriculum, compared to 20% at the beginning. Five of 15 reported teaching learners within the two-month post-curricular period, ranging from 5–30 students. The hands-on teaching was the most positively reviewed element of the curriculum. Conclusion: The SBML program successfully trained EPs on performing a comprehensive slit-lamp exam with promising results of downstream education to junior learners. We encourage other institutions to leverage SBML as a teaching modality for procedural-based training and advocate cross-discipline education initiatives.